2017
DOI: 10.3389/fimmu.2017.00954
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Osteoclasts in the Modulation of Bone Microenvironment and Immune Suppression in Multiple Myeloma

Abstract: Multiple myeloma (MM) is one of the most common forms of hematologic malignancy resulting from cancerous proliferation of mature malignant plasma cells (MPCs). But despite the real improvement in therapeutics in the past years, it remains largely incurable. MM is the most frequent cancer to involve bone due to the stimulation of osteoclast (OCL) differentiation and activity. OCLs have a unique capacity to resorb bone. However, recent studies reveal that they are not restrained to this sole function. They parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 121 publications
(150 reference statements)
0
26
0
5
Order By: Relevance
“…We further determined the benefit provided by this procedure on the analysis of OCL specific properties by comparing their expression levels of well-established OCL markers. Real-time quantitative PCR analysis revealed that, compared to their bone marrow CD11b + precursor cells, sorted murine ≥3N cells expressed very high RNA levels of Tcirg1 (a3 subunit of the V-ATPAse), Calcr (calcitonin receptor), Acp5 (TRAcP), Mmp9 (matrix metalloproteinase 9), Itgb3 (Integrin-β3) and Ctsk (cathepsin K) (Figure 3 ) demonstrating that sorted multinucleated cells have the molecular signature of mature OCLs ( 3 , 20 , 21 ). Importantly, sorted 1-2N cells expressed substantially and significantly lower levels of all OCL markers than sorted mature ≥3N OCLs.…”
Section: Resultsmentioning
confidence: 99%
“…We further determined the benefit provided by this procedure on the analysis of OCL specific properties by comparing their expression levels of well-established OCL markers. Real-time quantitative PCR analysis revealed that, compared to their bone marrow CD11b + precursor cells, sorted murine ≥3N cells expressed very high RNA levels of Tcirg1 (a3 subunit of the V-ATPAse), Calcr (calcitonin receptor), Acp5 (TRAcP), Mmp9 (matrix metalloproteinase 9), Itgb3 (Integrin-β3) and Ctsk (cathepsin K) (Figure 3 ) demonstrating that sorted multinucleated cells have the molecular signature of mature OCLs ( 3 , 20 , 21 ). Importantly, sorted 1-2N cells expressed substantially and significantly lower levels of all OCL markers than sorted mature ≥3N OCLs.…”
Section: Resultsmentioning
confidence: 99%
“…OCs regulate the bone marrow niches for hematopoietic stem cells ( 29 ), B-cell progenitors, and the proliferation of malignant plasma cells ( 30 ). They are capable of driving immune T-cell response toward immunosuppression or inflammation according to their origin and to their environment ( 31 , 32 ), and participate in the modulation of bone microenvironment and immune suppression in multiple myeloma ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…MM is characterized by the production of monoclonal intact immunoglobulins or immunoglobulin free light chains, leading on to renal failure, anemia, immunosuppression, and osteolytic bone disease, that occurs in most of these patients ( 3 ). The latter is, indeed, detected in ~70% of cases at the initial diagnosis of MM; it persists even in the absence of active disease, being a major cause of morbidity and mortality in MM patients ( 4 ). Despite the improvement in treatment options, during the clinical course of the disease 80–90% of patients experience skeletal-related events (SRE) such as bone pain (70–80% of the patients), spontaneous fractures (50–60%), hypercalcemia (15%), and spinal cord compression (2–3%) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is, indeed, detected in ~70% of cases at the initial diagnosis of MM; it persists even in the absence of active disease, being a major cause of morbidity and mortality in MM patients ( 4 ). Despite the improvement in treatment options, during the clinical course of the disease 80–90% of patients experience skeletal-related events (SRE) such as bone pain (70–80% of the patients), spontaneous fractures (50–60%), hypercalcemia (15%), and spinal cord compression (2–3%) ( 4 ). The development of bone lytic lesions is due to an alteration of the dynamic balance between bone-resorption and bone-formation, caused by an enhanced OC formation and activity, and an impaired osteoblast function ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation